EVALUATION OF HEALTH INFORMATION SYSTEMS IN THE HEALTH MEDICAL RECORD BIROBULI PALU - Mayapia, Melda; Chairin Nor, Andi Reza Alief; Kamaludin, Mufida (PROMOTIF: Jurnal Kesehatan Masyarakat, 2016)
ABSTRACT At this time, information technology is one of technology that is growing rapidly, with the advancement of information technology, data or information that provided can be fast to access, efficient and accurate. For example the results of advances in information technology is the development of the Internet network that allows all mankind worldwide using data provided or connected in the network together, meanwhile for Community Health Centers of Birobuli, data entry system still done manually, only BPJS already using a computerized system, so this study aims to determine the evaluation of health information systems at Community Health Centers of Birobuli Palu in medical record room.The method that used is qualitative, qualitative sense is depth research on employee community health center about training, processing SIK, activities program and benefits as well as developments SIK in community health centers of Birobuli Palu. The number of informants that used was 7 people of one key informant, three informant regular and three additional informants. The analysis of data using analytical approach (analysis content) with the matrix technique where the information was obtained on though in the table. It refers that input (for an educational background in the medical record average DIII of Public Health and for training of SIK at the community health center have never done the training because which provide training was from the Department of Health. Process (in data processing is done in two ways: manually and computerized, with a network system used is a LAN network, and for the delivery of report conducted by the online system and manual system). Output (many benefits of SIK for community health centers, so that the expected for community health center can immediately apply the SIMPUS program for SIK and provide training to SIK employees).The conclusion of this study is the application of SIMPUS program hasn’t been implemented at the community health center of Birobuli Palu because the community health center employee have never been training that given by the Department of Health. Expected to governments and health authorities can implement and optimize the use of SIK adequately in order to achieve maximum health services Keywords: Input, Process, Output, Health information systems